Zofka Kveder in Simona Semenič - Pezdirc-Bartol, Mateja (Amfiteater (Ljubljana), 2019)
Zofka Kveder (1878-1926) is not the first Slovenian woman writer nor the first Slovenian woman dramatist, yet her innovation and artistic power make her the most important Slovenian female author and dramatist of the end of the 19th and the first half of the 20th centuries. Simona Semenič (1975) is today the most visible, penetrating and innovative Slovenian dramatist - female or male -, which can be seen in the number of received awards, staged plays and invitations to international stages. The two dramatists also share the fact that their plays have been published in book editions - Kveder's collection Love from 1901 is even the first ever book collection of dramatic texts written by a female Slovenian author. Book editions of dramatic texts are a rarity today as well, so it is all the more refreshing that an author is able to publish as much as two in the same year, as did Simona Semenič in 2017, when do you hear me? and three dramas were published. If we compare the years of their births, we can see that they were born one hundred years apart. Since we are discussing the two most visible female dramatists of their time, the article compares their educational and creative paths and possibilities of earning a living as a writer in the past and today as well as draws certain parallels in their dramatic oeuvres. In many ways, Zofka Kveder's works, her life story and endeavours illustrate the usual career path of an intellectual at the break of the 20th century in the Austro-Hungarian Empire, when young women had yet to fight for their right to go to school and be educated. After completing her studies at the girls' lycee in Ljubljana, Kveder enrolled at the University of Bern, where female students without a high school diploma were eligible, but ultimately had to drop out because her financial resources were too scarce. With hard work, strong willpower and a constant thirst for knowledge, she gradually became a recognisable figure in the literary and cultural circles in Ljubljana, Prague and Zagreb, where she lived. She was a self-educated woman, who was painfully aware of the meaning of education, a question which, among others, she continually addressed in her literary and journalistic writings already in the 1899 article "On the Women's Issue", published in Slovenka magazine. She called attention to the problems faced by poor young women, who practically had no opportunities to be educated, as well as to the education of young girls, who are, compared to boys, preoccupied with everyday chores and later with housework and child care and thus have no free time to devote to reading, learning and developing their own interests, which Kveder depicted in one of the short stories from the collection The Mystery of a Woman. It can be gathered from the biographies of contemporary Slovenian women dramatists, including Simona Semenič, that practically all of them have been formally educated and that nearly all of them are involved in theatre, be it as actresses, directors, translators and, especially, as dramaturgs. Contemporary Slovenian dramatists thus have a thorough knowledge of dramatic theory and history, while their writing emerges and develops in close connection with practical theatre work. More female dramatists are creating now in the 21st century than ever before in the history of Slovenian literature, which is undoubtedly the result of the changed social circumstances as well as of the measures aimed at encouraging women's creativity with different calls and playwriting workshops; nevertheless, one of the key reasons for the gradual increase in the number of women dramatists through time is undoubtedly educational possibilities and thus a greater participation in the public space, which includes also the theatre. Zofka Kveder is the first professional Slovenian female writer to earn her living as a writer: she wrote literary and semi-literary works and worked as a translator and editor, with which she contributed significantly to the development of a new model of a professional writer. However, given that persevering in the position of an independent writer in an unfavourable environment took tremendous courage, she continually called attention to the women's issue and the role of women in the then society in both literary works as well as public appearances; her efforts can be seen as the beginnings of women's emancipation. Simona Semenič makes her living exclusively as a writer, too; besides writing plays, she is active as a director, performer, dramaturg and producer, she holds more and more playwriting workshops and other educational courses, making her one of the rare playwrights who persist in the position of professional freedom and autonomy. She is continually bringing to attention her status as a self-employed cultural worker, engaging at the same time with the questions of cultural politics and its absurd and unrealistic regulations, which is most visible in her dramatic text do me twice. The reading and interpretation of the authors' literary works reveal similarities especially at the level of autobiographical elements, the thematisation of women, 34 women's experience and the desire to break social taboos. However, there is a striking difference between them, resulting from two disparate literary and theatre aesthetics in two disparate time periods. Zofka Kveder's one-act plays Foreign Eyes, Winter Afternoon, At the Market, Broken, Love, The Drunk, Egoism and four-act plays The Right to Live and The Americans are bound to the realist poetics of serious, psychologically-driven drama. In terms of genre and style, her opus draws from the literary frames of reference of the end of the 19th century, although her one-act plays could be considered as modern forms of the time. On the other hand, the dramatic opus of Simona Semenič - the article focuses on the following plays the feast or the story of a savoury corpse or how roman abramovič, the character janša, julia kristeva, age 24, simona semenič and the initials z.i. found themselves in a tiny cloud of tobacco smoke; seven cooks, four soldiers and three sophias; sophia or while i almost always ask for more or a parable of the ruler and the wisdom; 5boys.si; i, the victim; 1981; this apple, made of gold; rowan, strudel, dance and more, etc. - entails a variety of genres and hybrid writing. Her texts are made up of an array of different discourses and are an interlacing of the tragic and the comic, irony and empathy, the horrific and the playful, which are nevertheless invariably permeated with a fundamental elusiveness, ambiguity and inconstancy. Simona Semenič is constantly calling into question the status of drama, seeking unconventional forms of writing, which will be heard in the world of mediatised culture. Zofka Kveder drew on the European literary tradition, which she enriched significantly with her literary works. She introduced new motifs and ideas to Slovenian literature, described without false sentimentality the position of women in the patriarchal society and their efforts to survive and be independent, spoke out against social prejudice and injustice, while continuously advocating for women's emancipation and their right to be educated. At the break of the 20th century, she tried to find a genuine female voice in Slovenian playwriting, which is in the beginning of the 21st century most visibly represented by Simona Semenič. Semenič addresses the contemporary spectator with innovative approaches to dramatic writing and the performative openness of her texts, confronting her or him with the present-day position of female artists, as well as bringing ethical reflections about the state of the modern world, keeping new textual strategies and formal innovation in her writing closely connected with the questions of reception and power of theatre today.
Keywords: dramatic form; dramatičarke; dramska forma; education; ethics; etika; female playwrights; izobrazba; Kveder, Zofka; motifs and themes; motivi in teme; poklicni status; professional status; Semenič, Simona; Slovenian drama; slovenska dramatika